Leveraging Tumor Microenvironment to Boost Synergistic Photodynamic Therapy, Ferroptosis Anti‐Tumor Efficiency Based on a Functional Iridium(III) Complex - Yu Pei; Yinzhen Pan; Zhijun Zhang; Jun Zhu; Yan Sun; Qian Zhang; Dongxia Zhu; Guangzhe Li; Martin R. Bryce; Dong Wang; Ben Zhong Tang (Advanced Science)
Abstract The tumor microenvironment (TME) severely limits the efficacy of clinical applications of photodynamic therapy (PDT). The development of a functional agent allowing full use of the TME to boost synergistic PDT and ferroptosis anti‐tumor efficiency is an appealing yet significantly challenging task. Herein, to overcome the adverse influence on PDT of hypoxia and high level of glutathione (GSH) in the TME, an imine bond is introduced into an Ir(III)‐ferrocene complex to construct a small molecule drug, named Ir‐Fc, for tumors’ imaging and therapy. The cleavage of the imine bond in the lysosome effectively disrupts the photoinduced electron transfer (PET) process, realizing the decomposition of Ir‐Fc into Fc‐CHO and Ir‐NH2. Fc‐CHO produces •OH by Fenton reactions under dark conditions and induces ferroptosis in tumor cells, and Ir‐NH2 shows prominent performance for type‐I and type‐II reactive oxygen species (ROS) production. Meanwhile, the ferroptosis pathway simultaneously consumes large amounts of GSH and produces O2 for effectively relieving hypoxia. These distinctive outputs make Ir‐Fc an exceptional molecule for effective tumor synergistic therapy. This study thus brings a new and revolutionary PDT protocol for practical cancer treatment.